HOW DO ABUSIVE SUPERVISION AND GENDER AFFECT EMPLOYEE CYBERLOAFING BEHAVIOR THROUGH EMOTIONAL EXHAUSTION? - Sagita, Ira; Bagis, Fatmah; Widhiandono, Hengky; Rahmawati, Ika Yustina (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study examines the role of abusive supervision and gender on cyberloafing with emotional exhaustion as a mediating variable. This study uses a quantitative approach with a questionnaire data collection method. This research was conducted on employees at maternity clinics in Purwokerto, totaling 140 respondents out of 212 employees. The sampling technique used was quota sampling by setting a quota based on the proportion of each maternity clinic. This research was conducted using Partial Least Square analysis. The results of this analysis calculate the percentage of the results of the demographic conditions of all employee respondents at maternity clinics in Purwokerto so that the calculations are evenly distributed. As a result, 140 respondents were collected from the sampling. By using a significant level of 5%, the results of the analysis calculation prove that Abusive Supervision has a significant positive effect on Cyberloafing and is dominated by female employees. Abusive Supervision has a significant positive effect on Emotional Exhaustion and is dominated by female employees. Emotional Exhaustion has a significant positive effect on Cyberloafing and is not influenced by gender. Meanwhile, the mediation results show that Emotional Exhaustion cannot mediate the relationship between Abusive Supervision and Cyberloafing and is not influenced by gender. The results of this study indicate that supervisors who treat employees harshly will make employees engage in cyberloafing behavior, but employees can control their emotions. Keywords: Abusive Supervision, Gender, Emotional Exhaustion, Cyberloafing